REACTIVE LYSIS: THE COMPLEMENT-MEDIATED LYSIS OF UNSENSITIZED CELLS : I. THE CHARACTERIZATION OF THE INDICATOR FACTOR AND ITS IDENTIFICATION AS C7 - Thompson, R. A. (The Rockefeller University Press, 1970)
This paper describes the characteristics of the indicator factor (I) which takes part in reactive hemolysis and its identification as the seventh component of complement. I was shown to be a beta globulin with a sediment coefficient of 5.7S and a molecular weight of about 140,000. Experiments on the depletion of I activity with anti-I antiserum or with activated R euglobulin showed that I was a late acting complement component necessary for the lysis of cells after the EAC142 stage. Complement component analysis of purified I fractions excluded all known components except C7. The physicochemical characteristics of I are compatible with published data on C7. The method of quantitation described represents a convenient method of testing for C7.